Relationship between tonic and phasic craving for alcohol. (June 2018) - Hartwell, Emily E.; Ray, Lara A.
Abstract: Background: Multiple measures are utilized to assess alcohol craving, often interchangeably. Little is known about the relationship between tonic and phasic craving. This study fills this gap in the literature by examining the association between tonic levels of alcohol craving and phasic craving for alcohol that is provoked by alcohol administration. Methods: Forty-three non-treatment seeking problem drinkers underwent an initial interview and two laboratory testing sessions, where either alcohol or a saline placebo was administered intravenously. Tonic craving was assessed via the Penn Alcohol Craving Scale (PACS) and Obsessive Compulsive Drinking Scale (OCDS) at the initial interview. Phasic craving was assessed during the laboratory sessions (i.e., alcohol and saline administrations, single blinded) at baseline and at 3 subsequent breath alcohol concentrations (0.02, 0.04, and 0.06 g/dl). Results: There was a main effect of PACS in predicting phasic craving across both saline and alcohol administration conditions ( p  < 0.05). The OCDS was predictive of phasic craving when alcohol, but not saline, was administered ( p  = 0.058); the obsessive subscale ( p  = 0.01), but not the compulsive subscale ( p  > 0.10), predicted phasic craving during alcohol, as compared to saline administration. Conclusion: In sum, tonic craving captured by the OCDS was predictive of phasic craving during alcohol administration whereas the PACS more generally captured the increase in phasic craving. Therefore, these measures of tonic craving may function differently in capturing the experience of phasic craving. Implications for the utilization of the PACS and OCDS as well as assessments of craving in alcoholism research are discussed. Highlights: Many measures are utilized, often interchangeably, to assess alcohol craving. Little is known about the relationship between provoked, phasic craving and long-term, tonic craving. Results indicated that the PACS predicted phasic craving, regardless of alcohol condition. The OCDS predicted phasic craving when alcohol was administered.